High prevalence of hyperkalemia in Brazilian chronic dialysis patients and differences across geographic regions - Nerbass,Fabiana Baggio (2022)
Abstract Introduction: Hyperkalemia is a common multifactorial condition of people on chronic dialysis and is associated with mortality. We aimed to inform and discuss the prevalence of hyperkalemia in a large population of chronic dialysis patients in Brazil and its geographic regions. Methods: Prevalence of hyperkalemia (serum potassium ≥6.0 mEq/L) was assessed in the Brazilian Dialysis Survey (BDS) in July 2019, an online survey of voluntary participation in which all dialysis centers registered at the Brazilian Society of Nephrology were invited. Results: Approximately one-third (n=263 of 805) of the Brazilian dialysis clinics participated. The prevalence of hyperkalemia in the whole population was 16.1% (n=7,457 of 46,193; 95%CI=15.8-16.5%,), and varied from 12.1% in the North to 18.7% in the Northeast. Conclusion: We found a high prevalence of hyperkalemia in a large Brazilian chronic dialysis population. A nationwide investigation of risk factors, treatment options, and whether this high prevalence contributes to dialysis mortality is warranted.